Organised Violence In The South Asian Region - JagritiKalita (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Organised violence can be of multiple forms and purposes, so common that it has become a part of modern life. Such type of violence are political in nature and may be sponsored by internal as well as external sponsors and includes both state and non-state actors. Terrorism, guerrilla wars, political assassinations, communal violence, police actions come under the sources of organised crime. I am going to discuss the various cases of organised crime in South Asia.